Hedgehog Signaling Regulates Nociceptive Sensitization - Babcock, Daniel T. (2011)
BACKGROUND: Nociceptive sensitization is a tissue damage response whereby sensory neurons near damaged tissue enhance their responsiveness to external stimuli. This sensitization manifests as allodynia (aversive withdrawal to previously nonnoxious stimuli) and/or hyperalgesia (exaggerated responsiveness to noxious stimuli). Although some factors mediating nociceptive sensitization are known, inadequacies of current analgesic drugs have prompted a search for additional targets. RESULTS: Here we use a Drosophila model of thermal nociceptive sensitization to show that Hedgehog (Hh) signaling is required for both thermal allodynia and hyperalgesia following ultraviolet irradiation (UV)-induced tissue damage. Sensitization does not appear to result from developmental changes in the differentiation or arborization of nociceptive sensory neurons. Genetic analysis shows that Hh signaling acts in parallel to tumor necrosis factor (TNF) signaling to mediate allodynia and that distinct transient receptor potential (TRP) channels mediate allodynia and hyperalgesia downstream of these pathways. We also demonstrate a role for Hh in analgesic signaling in mammals. Intrathecal or peripheral administration of cyclopamine (CP), a specific inhibitor of Sonic Hedgehog signaling, blocked the development of analgesic tolerance to morphine (MS) or morphine antinociception in standard assays of inflammatory pain in rats and synergistically augmented and sustained morphine analgesia in assays of neuropathic pain. CONCLUSIONS: We demonstrate a novel physiological role for Hh signaling, which has not previously been implicated in nociception. Our results also identify new potential therapeutic targets for pain treatment.